Pemetaan Areal Pertanian Hortikultura di Kabupaten Sumedang dalam Rangka Peningkatan Keberdayaan Petani - Saefudin, Bobby Rachmat; Rasmikayati, Elly (Universitas Galuh, 2024)
One area with high potential for horticultural commodity production is Sumedang Regency. However, in this district there is a decline in Horticultural commodity production. This is allegedly due to a decline in farmer performance in carrying out farming activities and a lack of farmer empowerment. In order to empower farmers, it is important to know information regarding the distribution of agricultural land and plants cultivated in Sumedang Regency. The aim of this research is to map the distribution of horticultural agricultural areas using cluster analysis as an effective analytical tool to see the distribution of horticultural agricultural areas based on data as an effort to increase the empowerment of farmers in Sumedang Regency. This research uses a quantitative design with descriptive statistical methods and secondary data, which is analyzed using cluster analysis with the help of the IBM SPSS 25 statistical application. Based on the results of the cluster analysis obtained by 5 clusters of horticultural agricultural areas in Sumedang Regency, the five clusters are frozen in the mapping of horticultural commodity clusters based on the harvested area in each sub-district in Sumedang Regency. This mapping provides several benefits in increasing empowerment, namely community empowerment, cooperation in the supply chain, improving agricultural risk management, exchanging innovations and transferring knowledge, increasing market access and increasing efficiency.